In vitro and in silico studies of compounds extracted from Elsholatzia cillata against bacteria Streptococcus pneumoniae and Streptococcus pyogenes - Nguyễn, Vĩnh Phú; Võ, Hoàng Bách; Hoàng, Thị Phương Nga; Trần, Quang Huy; Nguyễn, Đại Châu; Nguyễn, Thị Ái Nhung; Phan, Tứ Quý; Nguyễn, Thị Thanh Hải (Hue University Journal of Science: Natural Science, 2024)
The Elsholatzia cillata essential oil was extracted and characterized by gas chromatography-mass spectrometry (GC-MS) for compositional specificity. GC-MS analysis revealed the presence of 13 natural components in the essential oil (E1 - E13). The ability of active components that inhibit Streptococcus pneumoniae with 5XU1 protein and Strepcococcus pyogene with 4XCH protein was identified using in vitro and in silico studies. Evaluating the antibacterial ability of compounds in the Elsholatzia cillata essential oil under in vitro conditions that against S. pneumoniae and S. pyogenes exhibited that the results of inhibition zone diameter and minimum concentration inhibition (MIC) was 45 mm and 0.15625 µL.mL-1 on S.pneumoniae strain and 34 mm and 0.15625 µL.mL-1 on S. pyogenes strain, respectively. Molecular docking simulations confirmed the most effective inhibitors against proteins 5XU1 and 4XCH into the order of ligand-protein complexes E12, E9, E5, E11, E8 and E8, E11, E9, E10, E12.